Between Action and Emotional Survival During the COVID-19 era: Sensorimotor Pathways as Control Systems of Transdiagnostic Anxiety-Related Intolerance to Uncertainty - Goldstein Ferber, Sari; Shoval, Gal; Zalsman, Gil; Mikulincer, Mario; Weller, Aron (Frontiers in Psychiatry, 2021)
Objectives: The COVID-19 pandemic and aligned social and physical distancing regulations increase the sense of uncertainty, intensifying the risk for psychopathology globally. Anxiety disorders are associated with intolerance to uncertainty. In this review we describe brain circuits and sensorimotor pathways involved in human reactions to uncertainty. We present the healthy mode of coping with uncertainty and discuss deviations from this mode. Methods: Literature search of PubMed and Google Scholar. Results: As manifestation of anxiety disorders includes peripheral reactions and negative cognitions, we suggest an integrative model of threat cognitions modulated by sensorimotor regions: “The Sensorimotor-Cognitive-Integration-Circuit”. The model emphasizes autonomic nervous system coupling with the cortex, addressing peripheral anxious reactions to uncertainty, pathways connecting cortical regions and cost-reward evaluation circuits to sensorimotor regions, filtered by the amygdala and basal ganglia. Of special interest are the ascending and descending tracts for sensory-motor crosstalk in healthy and pathological conditions. We include arguments regarding uncertainty in anxiety reactions to the pandemic and derive from our model treatment suggestions which are supported by scientific evidence. Our model is based on systematic control theories and emphasizes the role of goal conflict regulation in health and pathology. We also address anxiety reactions as a spectrum ranging from healthy to pathological coping with uncertainty, and present this spectrum as a transdiagnostic entity in accordance with recent claims and models. Conclusions: The human need for controllability and predictability suggests that anxiety disorders reactive to the pandemic’s uncertainties are pathological reactions resulting from non-pathological human needs for coherence in life.